Mood and Memory Function in Ovariectomised Rats Exposed to Social Instability Stress - Al-Rahbi, Badriya; Zakaria, Rahimah; Hassan, Asma'; Muthuraju, Sangu; Mohammad, Wan Mohd Zahiruddin Wan (Hindawi Publishing Corporation, 2013)
This study aims to compare the effects of social instability stress on memory and anxiety- and depressive-like behaviour between sham-operated controls and ovariectomised (OVX) rats. Forty adult female Sprague-Dawley rats (8 weeks old) were randomly divided into four groups, (